Surface Carbonization of GaN and the Related Structure Evolution during the Annealing Process - 刘金龙 陈良贤 魏俊俊 黑立富 张旭 李成明 (Chinese physics letters, 2018)
To explain the stabilization mechanism of the carbon-ion-implanted GaN under the diamond growth environment,the luminescence characteristics and structure evolution correlative with sites’ carbon atoms located for highfluence carbon-ion-implanted Ga N are discussed. GaN is implanted with carbon ion using fluence of 2×1017 cm-2 and energy of 45 keV. Then the implanted samples are annealed at 800℃ for 20 min and 1 h under the N2 atmosphere. The luminescence characteristics of carbon-ion-implanted GaN are evaluated by photoluminescence spectrum at wavelength 325 nm. The lattice damage of Ga N is characterized by Raman spectrum and the corresponding vacancy-defect evolution before and after annealing is measured by slow positron annihilation. The results show that most of the carbon atoms will be located at the interstitial sites after carbon ion implantation due to the weak mobility. As the implanted samples are annealed, strong yellow luminescence is emitted and the vacancies for Ga(VGa) are reduced resulting from the migration of interstitial carbon（Ci） and formation of complexes(CGaand/or CGa-Ci) between them. As the annealing time is prolonged, the carbon ions accommodated by the vacancies are saturated, vacancy clusters with carbon atoms appear and the concentration of CGa diminishes, which will have an adverse effect on the diamond film nucleation and growth.